(untitled) (Kinesiology, 2017)
Hand grip strength (HGS) is important not only in its own right, but as an indicator of overall body strength and future outcomes as well. As we have found no studies on the HGS predictive models including Brazilian adults younger than 50 years of age, we aimed to develop a novel predictive equation using demographic and anthropometric attributes for subjects aged between 18 and 71 years. This is a cross-sectional study in which 203 (105 women) apparently healthy young and older adults were evaluated. A hydraulic dynamometer was used to measure HGS, according to the American Society of Hand Therapists recommendations. Several models were tested using age, body mass (W), body height (H), body mass index (BMI), level of physical activity (IPAQ) and gender as explanatory variables. Automated variable selection using the forward stepwise method was applied. The overall performance measures of the regression consisted of the R2 value adjusted for the number of variables retained in the proposed model, as well as of the standard error of the difference. Regression’s diagnosis using Pearson’s correlation coefficient, multicollinearity assessment and analysis of residuals were also performed to verify specific performance of the model. Statistical significance was considered at p<.05 for all analyses. Regarding the dominant (D) body side, the adjusted R2 value obtained by the stepwise method was .683. The variables age and IPAQ classification did not significantly increase the adjusted R2 value and therefore were excluded from the model (p>.100). For the non-dominant body side (ND), the adjusted R2 was .640. The final prediction models for the dominant body side was HGSPD=20.108×H+0.083×W+13.265×sexmale=1−8.737, whereas for the non-dominant body side it was HGSPND= 9.23×H+0.086×W+14.671×sexmale=1+5.904. Simple personal attributes, such as gender, body height and body mass can predict the expected values of HGS of the dominant and non-dominant upper limbs for Brazilian adults between 18 and 71 years. Key words: muscle strength, regression analysis, isometric contraction, hand strength